Assessing the impact of World Trade Center (WTC) exposures on post-bronchodilator lung function: Insights from WTC survivor population - Ziyue Wang; Jiacheng Ge; Yuyan Wang; Katherine Siu; Roberta Goldring; Beno Oppenheimer; Yongzhao Shao; Joan Reibman; Mengling Liu (PLoS ONE, 2026)
Objectives To assess the effects of World Trade Center (WTC) exposures, obesity, and smoking on post-bronchodilator (post-BD) lung function in WTC Survivors. Methods Data included 5,243 participants enrolled in WTC Environmental Health Center (WTC EHC) program between 2005 and 2022. WTC-related exposures included dust-cloud exposure and occupational/residential roles. Lung function included post-BD spirometry (FEV 1 , FVC) and impulse oscillometry (R 5 , R 20 , AX). Multivariable linear and quantile regressions assessed associations with WTC exposures, BMI, and smoking, adjusting for demographics. Results Dust-cloud exposure and Worker status were associated with elevated AX, R 5 , and R 20 , indicating small airway dysfunction. Spirometry showed minimal impact from dust exposure, though Workers had lower FEV₁ and FVC than Residents. Obesity and smoking were consistently linked to poorer lung function, with effect sizes surpassing WTC exposure. No significant interactions were found between BMI and WTC exposures. Conclusions WTC exposures are associated with small airway dysfunction, especially in Workers. Obesity and smoking independently worsen lung function, underscoring the importance of both environmental and physiological risk factors in disaster-exposed populations. Post-BD oscillometry adds critical sensitivity in detecting injury to small airways.